THE ROLE OF SMALL AND MEDIUM ENTERPRISES IN ECONOMIC DEVELOPMENT - Kalbinur Makhamatalieva, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Small and medium enterprises (SMEs) constitute the foundational architecture of virtually every economy on the planet. Representing approximately 90 percent of all registered  businesses  and  accounting  for  over  half  of  global  employment,  these enterprises occupy a position of indispensable structural significance in the creation of wealth, the distribution of economic opportunity, and the cultivation of innovation. Yet despite  their  collective  weight,  SMEs  remain  persistently  underexamined  in mainstream economic discourse, which has historically tilted toward the spectacular growth of large multinational corporations. This thesis undertakes a comprehensive investigation into the multi-dimensional role of SMEs in driving economic development across both advanced and emerging economies. Drawing upon data published by the World Bank, the International Labour Organization (ILO), the Organisation for Economic Co-operation and Development (OECD), and the International Finance Corporation (IFC), the study examines five core dimensions of SME contribution: employment generation, GDP output, innovation and technological  adoption,  poverty  alleviation,  and  regional  development.  The  thesis further identifies the principal challenges that constrain SME growth — with particular emphasis on the financing gap, regulatory burden, and digital adoption divide — and evaluates policy frameworks designed to address these structural impediments. The findings confirm that SMEs are not merely a feature of economic landscapes but  an  engine  of  their  transformation.  Their  capacity  to  absorb  labor,  generate enterprise,  reduce  inequality,  and  adapt  to  disruption  renders  them  central  to  the attainment  of  sustainable  development  goals.  The  thesis  concludes  with  a  set  of evidence-based policy recommendations directed at governments, development banks, and international organizations.